RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN PAKCOY (Brassica rapa L.) TERHADAP PEMBERIAN PUPUK GUANO - Ramadani, Ramadani; Wardati, Wardati; Silvina, Fetmi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research was aimed to determine the effect of guano application and get best doses for the growth and production. This research was carried out at Agriculture experimental station of Agriculture Faculty Riau University. This research was completed from april to may 2019. This research used a Completely Randomized Desaign ( CRD ). The treatments were aplication of guano at a plot of one m2, there were 0,6 kg.m-2, 0,9 kg.-2, 1,2 kg.m-2, 1,5 kg.m-2 dan 1,8 kg.m-2. The results showed that application of guano can increase plant height, leaves number, leaves large, plant weight per m2 and plant weight of eduble consumption per m2. Application of guano at 1,8 kg.m-2 showed best dose on each parameters.  Keywords : Pakchoy , Guano Fertilizer